Assessing the phenylketonuria (PKU) neonatal screening program and the incidence rates of PKU in Kerman County, Iran: a health system research - Esmat Rezabeigi Davarani; Fatemeh Mohseni Takaloo; Salman Daneshi; Peimaneh Sanjari; Narges Khanjani; Kiavash Hushmandi; Mehdi Raei (Hygeia Press di Corridori Marinella, 2022)
Background: Phenylketonuria (PKU) is a genetic autosomal recessive disorder, which, if not treated on time, can lead to mental retardation and severe developmental delay. The aim of this study was to assess the PKU neonatal screening program in Kerman County, Iran.  Methods: This was a health system research study carried out on all newborns screened for PKU from 2012 to 2018 in Kerman. Data were extracted from the Comprehensive Social Genetics Program forms, genetic records, and the national form for investigation of genetic disease incidence.  Results: Totally, 121,533 newborns were screened. 108,972 (89.7%) were Iranian, and 12,561 (10.3%) were non-Iranian. Screening coverage in the Iranian population was 92.1%. 80.9% of Iranian and 62.8% of non-Iranian newborns were screened from 3 to 5 days of age. Timely screening of newborns in the Iranian and non-Iranian populations in 2012 was 70.0% and 46.9%, and in 2018, it was 90.2% and 75.1%, respectively. The first visit at the PKU treatment center in 30.7% of Iranian and 33.3% of non-Iranian neonates was before 14 days of age. In the Iranian population residing in Kerman, the incidence rate of PKU was estimated to be 1.35 per 10,000 live births. 62.5% of parents of Iranian and 100% of parents of non-Iranian PKU patients were relatives.  Conclusion: PKU screening coverage in Kerman is relatively acceptable, and most newborns were screened on time. Timely screening of newborns in both populations has increased since the beginning of the program until the time of this study. Interventions are required to improve early diagnosis and start treatment during the first 2 weeks of life. The incidence of PKU in Kerman County is approximately equal to the national average. Due to the fact that most parents of PKU patients are relatives, increasing awareness to prevent consanguineous marriages can be effective in decreasing the incidence of this disease.